Strategies to enhance oral delivery of amphotericin B: a comparison of uncoated and enteric-coated nanostructured lipid carriers - Pataranapa Nimtrakul; Pakawadee Sermsappasuk; Waree Tiyaboonchai (Taylor & Francis Group, 2020)
The oral delivery of amphotericin B (AmB) has remained a challenge due to its low solubility, permeability, and instability in gastric acidic pH. To solve these issues, herein, we reported a novel approach of using nanostructured lipid carriers (NLCs) and NLCs coating with Eudragit®L100-55 (Eu-NLCs) for the oral delivery of AmB. This study aimed to compare their ability in protecting the drug from degradation in gastrointestinal fluids and permeation enhancement in Caco-2 cells. Uncoated NLCs and Eu-NLCs possessed a mean particle size of ∼180 and ∼550 nm, with a zeta potential of ∼−30 and ∼−50 mV, respectively. Both NLCs demonstrated an AmB entrapment efficiency up to ∼75%. They possessed significantly greater AmB water solubility than the free drug by up to 10-fold. In fasted state simulated gastric fluid, Eu-NLCs provided significantly greater AmB protection from acidic degradation than uncoated NLCs. In fasted state simulated intestinal fluid, both uncoated and Eu-NLCs showed a fast release characteristic. Caco-2 cells permeation studies revealed that uncoated NLCs provided significantly higher apparent permeation coefficient (Papp) value than Eu-NLCs. Moreover, after 6 months of storage at 4 °C in the absence of light, the physicochemical stabilities of the lyophilized uncoated and Eu-NLCs could be maintained. In conclusion, the developed NLCs and Eu-NLCs could be a potential drug delivery system in improving the oral bioavailability of AmB.